Reconceptualizing Teacher Professionalism in Islamic Primary Education: Integrating Islamic and Global Frameworks - Anis Fauzi; Lilis Lisdiawati; Piping Muhtofin; Rifyal Lugowi; Mikdar Rusdi (Journal of Islamic Education Research, 2026)
This study critically reconceptualizes teacher professionalism and performance in Islamic primary education by positioning Islamic intellectual traditions in dialogue with contemporary global educational frameworks. Despite extensive research, dominant models of teacher professionalism remain largely technocratic, systematically privileging measurable competencies while neglecting ethical and spiritual dimensions. This study employs a systematic literature review (SLR) following PRISMA guidelines, analyzing peer-reviewed articles retrieved from Scopus, Web of Science, and Google Scholar, published between 2016 and 2025. The study selection process involved identification, screening, eligibility assessment, and final inclusion stages, ensuring methodological transparency and rigor. The data were analyzed using thematic analysis to identify key patterns related to teacher professionalism, performance, and learning quality. The findings reveal that teacher professionalism in Islamic education is a multidimensional construct integrating pedagogical competence, professional expertise, and ethical-spiritual values such as adab, amanah, and ihsan. Teacher performance is shaped by both internal factors, including motivation and psychological well-being, and external conditions such as institutional support and professional learning environments. Furthermore, the results demonstrate that the interaction between professionalism and performance significantly enhances learning quality, particularly in fostering holistic student development. The novelty of this study lies in its integrative framework, which challenges dominant technocratic models by embedding ethical and spiritual dimensions within contemporary theories of teacher effectiveness. This study contributes theoretically by advancing a more holistic and context-sensitive understanding of teacher professionalism and practically by informing the design of teacher development programs that are both globally informed and ethically grounded.